A construção de lideranças políticas: alianças, redes de relações e dominação em Sergipe - Bomfim, Fagner dos Santos (2024)
The aim of this thesis is to analyze how political leaders are formed. From this perspective, it analytically problematizes the relationship between the groups and groupings that these leaders belong to and the resources that they accumulate over the course of their careers. It is tassumed that in order to analyze this construction, it is necessary to take into account two intersecting elements: the relationship with groups and groupings, and the individual aspects of this leadership, in plain English, the social resources they accumulate throughout their career and in the construction of their political career. For the purpose of the empirical universe, we have analyzed the political clusters and groupings to which the governors of the state of Sergipe were elected since the re-democratization belonged (1983-2022). Therefore, it specifically aims to: a) present a socio-history of Sergipe's political leaders, their trajectories and political careers within the groups, groupings and political blocs they were part of; b) construct a sociogenesis of the spaces of representative action (the political parties, groups and groupings) which these actors build as their significant networks of relations and domination in the craft of politics; c) examine how social resources (family, professional, political, cultural and militant), alliances, networks of relationships and domination (friendships, nominations, patronage, etc.) contribute to the construction of these political leaders; d) build a sociographic profile of these political leaders, taking into account the social resources used and reconverted into qualitative assets for their professional careers; and e) advance the contribution of sociological interpretation on the importance of alliances, networks of relationships and domination for the construction of professional careers in politics. The methodological elements consisted of: documentary sources, bibliographic dictionaries, such as CPDOC, the websites of ALESE, the Federal Chamber and the Federal Senate; personal websites and profiles on social networks (Instagram, Facebook and Twitter), memoirs, biographies and autobiographies, press materials (newspapers, television, radio and the internet), photographs, etc. In addition, building a database on the trajectories of these leaders. The thesis is divided into four chapters: (i) a theoretical debate on political elites, personalist forms of leadership in Latin America, as well as presenting the Parentela as a significant analytical concept for understanding the system of alliances developed in Brazil, in addition to the condition of interpreting coalitions in the formation of political groupings and blocs; (ii) a socio-history of political leaders, groups and groupings, from the Proclamation of the Republic (1889) to the Military Regime (1964); (iii) presents an analysis of how groups and groupings changed over these periods and how these have changed the social resources used for political consecration in this period from the Military Regime (1964) to redemocratization and in the years 2022; finally, (iv) presents a sociographic profile of Sergipe's political leaders and their composition among family-based group leaders, by belonging to a professional political group and by links to political militancy. In this sense, the thesis demonstrates that the construction of political leadership does not only involve the mere personalistic and elective condition of building a political actor into a leader, but a set of elements that intersect and allows the capitality of transformation into political leadership. It is through the social resources that are activated and reconverted into electoral assets, as well as the logic of the formation of political groups and groupings, to which these actors become part and build their alliances, networks of relationships and domination in national, state and local politics.